Development of Thermoregulation Model of Surgical Patient and Heat Exchange with Air Condition in the Operating Room. (2017) - Romadhon, Rahmat; Rinata, Addin Dinda; Suprijanto,; Bindar, Yazid; Soelami, F.X. Nugroho
Abstract: One of the main effect of anesthesia in surgical patients is hypothermia. Its effectpossibility causes the declining of the immune system and surgical site infections. The anesthetic will affect the body's thermoregulatory system that reduced the generation of heat from the body. The lower temperature of air condition in the operating room will increase heat loss from the body and exacerbate the drop of core body temperature. This study was conducted to evaluate the response of surgical patient's body who experience the effects of anesthesiain varied air conditions. The model of thermoregulation and heat exchanges are developed to determine the distribution of body temperatures. The bioheat equation is modified regarding to the change of its conditions and implemented on the spherical and cylindrical models of the body. Thermoregulation models consist of conduction heat transfer at each tissue element with heat generation from metabolism and blood perfusion and heat exchange between skin and ambient air. Model simulations conducted during 30 minutes with applying time dependent conditions. The surrounding temperature is set at 21, 23, and 25°C where for each condition the air velocity on the body surface is set at 0.2 and 0.4m/s. Results of simulation show that the temperature on the upper side of the body is higher than the lower side and the temperature of the surgical patient who affected by anesthesia is lower than the normal people. On varied condition the upper side of body temperature are 33.4 o C, 33.8 o C and 34.4 o C respectively and indicates that radiation is the dominant mode of heat exchange between body and surrounding.